Educational Progress as a Booster of Economic Growth in Indonesia - Istiqomah Ahsanu Amala; Nabilah Arrahmah; Endah Nur Amalina (Universitas Bangka Belitung, 2022)
Abstract: Increasing population growth as a demographic bonus in Indonesia needs to be balanced with improving the quality of human capital so that the demographic bonus can increase economic growth. Improving the quality of human capital investment takes a long time to produce tangible results, but the benefits will last longer for economic growth. The purpose of this research is to find out the link between education in boosting economic growth and formulate efforts that can be made to advance education in Indonesia. The research method used in this research is Systematic Review (SR) with Narrative Review (NR) research type. In realizing the education progress in Indonesia, the government can seek planned education based on the social demand approach, economic return approach, employment generation approach, and supports education for girls' and women's rights. Support from the government is one of the primary keys to developing human capital. Even so, every aspect of the educational environment needs to support and contribute to realizing progress in education together to boost economic growth in Indonesia.